Providers’ knowledge, attitudes, and practices related to colorectal cancer control in Brazil() - Puricelli Perin, Douglas M. (Prev Med, 2015)
In Brazil, colorectal cancer (CRC) is the fourth most common cause of cancer-related death among men, and the third most common among women. We aimed to examine CRC screening-related knowledge, attitudes, and practices among physicians and nurses working in Brazil’s network of health units, and to describe the capacity of these units for CRC screening. In 2011, 1600 health units were randomly selected from all 26 states and the Federal District. One coordinator and one health care provider were selected for the interview. Response rates were 78% for coordinators, 34% for physicians, and 65% for nurses. The Brazilian National Cancer Institute (INCA) recommendations for CRC screening were not often used in the health units, but screening outreach and use of CRC exams were more common in units that were using them. Physicians and nurses differed in most characteristics, and in their knowledge, attitudes, and practices of CRC screening. Forty-seven percent of physicians reported not conducting CRC screening compared to 65% of nurses. Fecal occult blood test was most often used by physicians and nurses, but fewer physicians than nurses perceived this exam as very effective in reducing CRC mortality. Physicians’ gender, years since graduation, and geographical region of practice in Brazil were associated to CRC screening practice. The findings may reflect the low influence of INCA CRC screening recommendations, physicians receiving their medical education when CRC burden in Brazil was of low concern, and the lack of CRC screening capacity in some regions of Brazil.